Preconcentration of Aluminum by Dual-cloud Point Extraction and its Determination by Inductively Coupled Plasma-optical Emission Spectrometry - Mortada, Wael I.; Alharthi, Sarah (Current Analytical Chemistry, 2021)
Background: The combination of cloud point extraction (CPE) with inductively coupled plasma-optical emission spectrometry (ICP OES) is limited due to the effect of organic diluent and surfactant on the signal. Methods: A dual-CPE process (d-CPE) was presented for the enrichment of aluminum (Al3+), before determination by ICP OES, to exclude the effect of surfactant and organic solvent on the ICP OES signal. The analyte was firstly extracted into Triton X-114 rich phase as a gallic acid complex. In the second step, Al3+ was back extracted into an aqueous phase of HNO3 that was introduced into ICP OES. The effects of pH, concentrations of gallic acid and Triton X-114, incubation temperature and time, centrifugation conditions and the concomitant ions were evaluated. Results: The method displayed good analytical characteristics at the optimum conditions. An enrichment factor of 49.5 was achieved. The linear calibration graph was obtained from 1.0 to 1000 μg L-1 and the detection limit was 0.31 μg L-1. The relative standard deviation was 2.3% (50 μg L-1 Al3+, n = 10). Quantitative recoveries ranging from 96.0 to 100% were obtained for spiked water and geological samples. This procedure was used efficiently for preconcentration and quantification of Al3+ in various samples by ICP OES. Conclusion: The presented procedure is simple, rapid, accurate, and safe. It can be used for the determination of Al3+ by ICP OES in samples with complicated matrices.
Keywords: Dual-cloud point extraction